COVID-19 PREVENTION SIGNS IN THE INDONESIA'S SUPER PRIORITY TOURIST DESTINATION - Lery Prasetyo; Ketut Artawa; I Wayan Mulyawan; Ketut Widya Purnawati; I Wayan Suardiana (STABN Raden Wijaya Wonogiri, 2023)
After a long struggle against Covid-19 for more than a year, the spread of COVID-19 in Indonesia gradually decreased and was considerably under control. Several public places, including some tourist destinations, were allowed to re-open. The Ministry of Tourism and Creative Economy made 20 tourist attractions for trial, including the Borobudur temple, the world’s largest Buddhist temple. It is carried out cautiously and under strict health protocols procedure. Implementing health protocol regulations was encouraged by making and placing many protocol signs in strategic places. The aim of this study was to identify and investigate the compositions meaning of the COVID-19 prevention sign at Borobudur Temple. The data were collected through the documentation method with photographic technique. The result showed that all signs have real and ideal information value. Salience signs appear as a result of a variety of fascinating text and images. The framing of the sign is presented in centered/circular with a linear and nonlinear composition. Overall, the signs proved the management of Borobudur temple’s strong commitment to opening the site with strict protocols to prevent the spread of COVID-19 in the Borobudur area.